International prevalence and risk factors evaluation for drug-resistant Streptococcus pneumoniae pneumonia. Issue 4 (October 2019) - Aliberti, Stefano; Cook, Grayden S.; Babu, Bettina L.; Reyes, Luis F.; H. Rodriguez, Alejandro; Sanz, Francisco; Soni, Nilam J.; Anzueto, Antonio; Faverio, Paola; Sadud, Ricardo Franco; Muhammad, Irfan; Prat, Cristina; et al.
Highlights: Streptococcus pneumoniae was the most frequently identified pathogen in a cohort of patients with community acquired pneumonia (CAP) (268/3193 [8.3%]). The global prevalence of drug resistant S. pneumoniae CAP (DRSP-CAP) was 1.3%. Macrolide resistance was the most frequently identified in subjects with DRSP-CAP (0.6%) followed by penicillin resistance (0.5%). The risk factors associated with specific antibiotic resistance were: asthma (for penicillin and macrolide), liver disease (for tetracycline resistance) and non-cystic fibrosis bronchiectasis (for penicillin resistance). Summary: Objective: Streptococcus pneumoniae is the most frequent bacterial pathogen isolated in subjects with Community-acquired pneumonia (CAP) worldwide. Limited data are available regarding the current global burden and risk factors associated with drug-resistant Streptococcus pneumoniae (DRSP) in CAP subjects. We assessed the multinational prevalence and risk factors for DRSP-CAP in a multinational point-prevalence study. Design: The prevalence of DRSP-CAP was assessed by identification of DRSP in blood or respiratory samples among adults hospitalized with CAP in 54 countries. Prevalence and risk factors were compared among subjects that had microbiological testing and antibiotic susceptibility data. Multivariate logistic regressions were used to identify risk factors independently associated with DRSP-CAP. Results: 3, 193 subjects were included in the study. The global prevalence of DRSP-CAP was 1.3% and continental prevalence rates were 7.0% in Africa, 1.2% in Asia, and 1.0% in South America, Europe, and North America, respectively. Macrolide resistance was most frequently identified in subjects with DRSP-CAP (0.6%) followed by penicillin resistance (0.5%). Subjects in Africa were more likely to have DRSP-CAP (OR: 7.6; 95%CI: 3.34-15.35, p<0.001) when compared to centres representing other continents. Conclusions: This multinational point-prevalence study found a low global prevalence of DRSP-CAP that may impact guideline development and antimicrobial policies.